Reliability of force-velocity relationships during deadlift high pull - Lu, W.; Boyas, S.; Jubeau, M.; Rahmani, A. (Sports Biomechanics, 2019)
This study aimed to evaluate the within- and between-session reliability of force, velocity and power performances and to assess the force-velocity relationship during the deadlift high pull (DHP). Nine participants performed two identical sessions of DHP with loads ranging from 30 to 70% of body mass. The force was measured by a force plate under the participants` feet. The velocity of the `body + lifted mass` system was calculated by integrating the acceleration and the power was calculated as the product of force and velocity. The forcevelocity relationships were obtained from linear regression of both mean and peak values of force and velocity. The within- and betweensession reliability was evaluated by using coefficients of variation..(CV) and intraclass correlation coefficients (ICC). Results showed that DHP force-velocity relationships were significantly linear (R² > 0.90,.p < 0.05). Within sessions and between sessions, mean and peak forces during DHP showed a strong agreement (CV < 3%, ICC > 0.94),mean and peak velocities showed a good agreement (CV < 9%, 0.78 < ICC < 0.92). It was concluded that DHP performance and its force-velocity relationships are highly reliable and can therefore be utilised as a tool to characterise individuals` muscular profiles.